Energy management of a concentrated photovoltaic−thermal unit utilizing nanofluid jet impingement in existence of thermoelectric module - M. Sheikholeslami; Z. Khalili (Engineering Applications of Computational Fluid Mechanics)
To generate a concentrated photovoltaic–thermal (CPVT) unit system, linear Fresnel concentrators have been attached to a PV unit and a thermoelectric generator (TEG) has been combined in this work to boost productivity. In the presence of concentrators, the temperature of the silicon layer increases. While electrical output is enhanced for the CPVT unit, the non-uniform isotherms can decrease the lifetime of the panel, so confined jets of alumina–water nanofluid have been applied for cooling. To validate the numerical code, previous papers were examined and good accommodations were reported. Various values of the inlet temperature (Tin) and velocity (Vin) of jets have been analysed. The impacts of installing concentrators on overall performance and CO2 mitigation have been investigated. An increase in Vin leads to an incremental increase in thermal performance of about 4.2% and thermal uniformity is enhanced by about 13.91%. The thermal power of the system is enhanced by about 2.19 times as a result of adding concentrators. Also, the PV power is enhanced by 86.22% in the presence of the reflectors. With the increase in Tin, the thermal and electrical performance decrease by about 19.95% and 5.24%, respectively. Installing concentrators enhances the overall performance by about 6.55%. After 10 years, the amount of CO2 mitigation for the CPVT-TEG system reaches 148.28 ton.